Single- and multi-photon-induced ultraviolet excitation and photodissociation of CH3I probed by coincident ion momentum imaging. Issue 14 (24th March 2023) - Ziaee, Farzaneh; Borne, Kurtis; Forbes, Ruaridh; P., Kanaka Raju; Malakar, Yubaraj; Kaderiya, Balram; Severt, Travis; Ben-Itzhak, Itzik; Rudenko, Artem; Rolles, Daniel
Abstract : The UV-photodissociation of methyl iodide (CH3 I) and other competing processes are studies by time-resolved Coulomb explosion imaging. Abstract : The UV-induced photodissociation dynamics of iodomethane (CH3 I) in its A-band are investigated by time-resolved coincident ion momentum imaging using strong-field ionization as a probe. The delay-dependent kinetic energy distribution of the photofragments resulting from double ionization of the molecule maps the cleavage of the carbon–iodine bond and shows how the existence of a potential well in the di-cationic potential energy surfaces shapes the observed distribution at small pump–probe delays. Furthermore, the competition between single- and multi-photon excitation and ionization of the molecule is studied as a function of the intensity of the UV-pump laser pulse. Two-photon excitation to Rydberg states is identified by tracking the transformation of the delay-dependent singly-charged iodomethane yield from a pure Gaussian distribution at low intensity to a Gaussian with an exponentially decaying tail at higher intensities. Dissociative ionization induced by absorption of three UV photons is resolved as an additional delay-dependent feature in the kinetic energy of the fragment ions detected in coincidence.